Two conditional tsA mutant simian virus 40 T antigens display marked differences in thermal inactivation. - Reynisdóttir, I (1992)
We have characterized the simian virus 40 (SV40) origin-containing DNA (ori-DNA) replication functions of two SV40 conditional mutant T antigens: tsA438 A-V (tsA58) and tsA357 R-K (tsA30). Both tsA mutant T antigens, immunopurified from recombinant baculovirus-infected insect cells, mediated replication of SV40 ori-DNA in vitro to similar extents as did wild-type T antigen in reactions at 33 degrees C. However, at 41 degrees C, the restrictive temperature, while tsA438 T antigen still generated substantial levels of replication products, tsA357 T antigen did not support any detectable DNA synthesis. Furthermore, preincubation for approximately fourfold-longer time periods at 41 degrees C was required to heat inactivate tsA438 T antigen than to heat inactivate tsA357 T antigen. Unexpectedly, results of analyses of the various DNA replication activities of the two mutant T antigens did not correlate with results from ori-DNA replication reactions. In particular, although tsA357 T antigen was incapable of mediating replication at 41 degrees C at all protein concentrations examined, it displayed either wild-type levels or only partial reductions of the several T-antigen replication-associated activities. These data suggest either that tsA357 T antigen is defective in an as yet unidentified replication function of T antigen or that the combination of its partial defects result in a protein that is unable to support replication. The data also show that two conditional mutant T antigens can be markedly different with respect to thermal sensitivity.